A cross-sectional study on the correlations between floating toe, plantar arch posture, and body composition in 8-year-old children. Issue 7 (October 2022) - Wako, Masanori; Fujimaki, Taro; Koyama, Kensuke; Furuya, Naoto; Shinohara, Ryoji; Otawa, Sanae; Kobayashi, Anna; Horiuchi, Sayaka; Kushima, Megumi; Yamagata, Zentaro; Haro, Hirotaka
Abstract: Background: Floating toe (FT): inadequately in contact with the ground and flexible flat foot (FFF) are frequently seen in children. According to some reports, inadequate foot muscle strength may cause FT or FFF.Therefore, a relationship may exist between arch formation, FT, and pedal muscle strength. This study aimed to evaluate the correlation of FT with plantar arch posture and body composition, including overall muscle mass. Methods: We conducted our own cohort study in addition to the Japan Environment and Children's Study conducted by the Ministry of the Environment, Japan. Out of 705 eight-year-old children participating in this adjunct study, 578 with recorded footprints were included. Body composition (body weight, body fat percentage, and predicted muscle mass) was assessed using body composition analyzer. Presence of FT or FFF was evaluated using foot pressure plate. We calculated the FT score (small FT score indicates insufficient ground contact of the toes) and the Chippaux-Smirak Index (CSI) using images of the plantar footprint. Results: The FT score (an indicator of FT) showed no significant correlation with CSI (an indicator of plantar arch posture). Moreover, no significant correlations between the predicted muscle mass, FT score, and CSI were observed. Conclusions: This is the first report that assessed the relationship of FT with plantar arch posture and body composition in children. This study indicated that muscle strength might not be a major factor for FT and FFF development in children.